Screening Mental Well-Being in High Demand Occupational Settings in South Africa - Charles H Van Wijk (European Scientific Journal, ESJ, 2017)
This study considered promoting well-being of employees in high demand occupational positions, through the screening of mental well-being. The numerous challenges to such monitoring in a multi-lingual developing country like South Africa – where this study was conducted – requires a tool that can screen for the mental well-being of at-risk individuals, in order to timeously refer vulnerable persons to appropriate mental health support services. This paper explored whether the State-Trait Personality Inventory-Trait Scales (STPI-T) can be used fairly to monitor the well-being of young adult South Africans in high demand occupational settings. The self-report scales were administered to a non-clinical sample (women=392, men=521) aged 20 to 40 years, and their responses were analyzed with MANOVA and a ROC analysis. The main findings of the study indicated that contextualised norms are required (and were provided for the sample studied), develop per specific national and occupational environment; and that socio-demographic variables like gender, age, and language had limited effect on scale responses in this select sample. The scales effectively identified vulnerable individuals, comparable to psychological interviews. Scale scores were highly homogenized, facilitating identification of outliers which may indicate poorer mental health, thus enabling further referral for appropriate support. In conclusion, the study provides support for the use of the SPTI-T to promote the well-being of employees in multi-lingual high demand occupational settings, through regular monitoring and early identification of risk for poor mental health.